Can Financial Aid Help to Address the Growing Need for STEM Education? The Effects of Need‐Based Grants on the Completion of Science, Technology, Engineering, and Math Courses and Degrees. (16th November 2017) - Castleman, Benjamin L.; Long, Bridget Terry; Mabel, Zachary
Abstract: Although workers in science, technology, engineering, and math (STEM) fields earn above‐average wages, the number of college graduates prepared for STEM jobs lags behind employer demand. A key question is how to recruit and retain college students in STEM majors. We offer new evidence on the role of financial aid in supporting STEM attainment. Exploiting a regression discontinuity that allows for causal inference, we find that eligibility for need‐based financial aid increased STEM credit completion by 20 to 35 percent among academically‐ready students in a large, public higher education system. These results appear to be driven by shifting students into STEM‐heavy course loads, suggesting aid availability impacts the academic choices students make after deciding to enroll. We also find suggestive evidence that aid offers increase degree attainment in STEM fields, although we cannot rule out null impacts on STEM degree production.